Naturopathic Therapy Efforts: Potential Gingerol Content in Ginger (Zingiber officinale) As An Antidiabetic - Fitri Yani Rahmawati; Yuli Rahmawati Utami; Muna Az Zahra; Ida Maryati (Journal of Nursing Care, 2022)
Diabetes Mellitus (DM) is caused by unhealthy lifestyle habits and one of the treatment efforts is naturopathic therapy by utilizing the gingerol content in red ginger (Zingiber officinale). The role of nurses in complementary fields as providers of interventions can improve public health status. This narrative review aims to interpret research the potential content of red ginger as an antidiabetic. The research were carried out by identifying research questions, "what is the content of gingerol in red ginger as antidiabetic?". Literature search using EBSCO, PubMed, Springer Experiment, and Neliti. Used keywords ''Nathuropathic therapy efforts AND Gingerol OR Red ginger OR Zingiber officinale AND Antidiabetic'' obtained 140 articles. Then sorted with inclusion and exclusion criteria, so we obtained 7 articles stated that red ginger concerning intake doses per day of 1-3 and 6 grams can lower blood glucose which contains gingerol which stimulates insulin secretion and improves glucose tolerance. Red ginger as a natural ingredient is certainly easy to find, practical, has no side effects, and economical. It is necessary to conduct further research regarding the type of red ginger and the dosage that adjusted to the habits of the Indonesian people so not to cause confusion regarding the application process